2011
DOI: 10.1038/gt.2011.29
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage LXRα gene therapy ameliorates atherosclerosis as well as hypertriglyceridemia in LDLR−/− mice

Abstract: Liver X receptors (LXRs) are implicated in the regulation of cholesterol homeostasis, inflammatory response and atherogenesis. Administration of LXR agonists inhibits the progress of atherosclerosis, and also increases plasma triglyceride levels, representing an obstacle to their use in treating this disease. The objective of this study was to develop an alternative approach that could overcome this obstacle. Eight-week-old low-density lipoprotein receptor-deficient (LDLR À/À ) mice were transplanted with hema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 37 publications
0
5
0
1
Order By: Relevance
“…To gain insight into the cellular mechanisms controlled by LXRα signaling that lead to the development of MZ macrophages, we overexpressed LXRα in hematopoietic stem cells (HSCs) using a myeloid specific lentiviral system 27,28 . First, we examined the expression of the green fluorescent protein (GFP) in blood monocytes obtained from mice transplanted with HSC-enriched BM cells that were previously transduced with the myeloid specific lentivirus.…”
Section: Resultsmentioning
confidence: 99%
“…To gain insight into the cellular mechanisms controlled by LXRα signaling that lead to the development of MZ macrophages, we overexpressed LXRα in hematopoietic stem cells (HSCs) using a myeloid specific lentiviral system 27,28 . First, we examined the expression of the green fluorescent protein (GFP) in blood monocytes obtained from mice transplanted with HSC-enriched BM cells that were previously transduced with the myeloid specific lentivirus.…”
Section: Resultsmentioning
confidence: 99%
“…These constructs were driven by the MSP, thereby favoring enhancement of both the therapeutic efficacy and safety of neurotrophic factor gene therapy by restricting the expression of the transgene to microglial precursor cells (monocyte/macrophage) [2]. To confirm the expression of NTN in the transduced marrow cells aliquots of MSP-NTN and MSP-GFP transduced cells were cultured in macrophage medium [17] for seven days to transform them into macrophages. Immunocytochemical staining revealed that >95% of the MSP-NTN transduced macrophages expressed NTN in their cytoplasm, whereas no NTN staining was observed in MSP-GFP transduced macrophages (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…LXR agonist activation inhibits the induction of pro-inflammatory cytokines through a mechanism involving transrepression [ 63 ]. In atherogenic Ldlr −/− mice, selectively increasing LXRα in macrophages leads to reductions in plasma inflammatory cytokines, IL6 and TNFα, and atherosclerotic lesion development [ 82 ]. Moreover, in the absence of cholesterol efflux pathways mediated by Abca1/g1 -deficient macrophages, LXR agonism nonetheless decreased lesion area, complexity, and inflammatory cell infiltration, including plasma levels of the chemokine, MCP1 [ 67 ].…”
Section: Systemic Effects Of Lxr Signaling In the Development And Promentioning
confidence: 99%